Chlamydia trachomatis Infection in HIV-Infected Women: Need for Screening by a Sensitive and Specific Test. (5th December 2013) - Bhattar, Sonali; Bhalla, Preena; Chadha, Sanjim; Tripathi, Reva; Kaur, Ravinder; Sardana, Kabir
Abstract : Reproductive tract infection (RTIs)/sexually transmitted infections (STIs) are recognized as a major public health problem, particularly due to their relationship with HIV infection. Early detection and treatment of Chlamydia trachomatis infection (CTI) among HIV-infected and HIV-uninfected women may impact heterosexual HIV transmission. A total of 120 participants were enrolled: 30 HIV seropositive women with symptoms of RTIs, 30 HIV seropositive women without symptoms of RTIs, 30 HIV seronegative women with symptoms of RTIs, and 30 HIV seronegative women without symptoms of RTIs. One endocervical swab was collected from all participants and CTI was detected by real-time PCR (COBAS TaqMan CT Test, v2.0). CTI was detected in 4 (6.67%) HIV-infected women and in 1 (1.67%) HIV-uninfected woman (OR 4.214; 95% CI 0.457–38.865). Vaginal discharge was present in almost half of HIV-infected and HIV-uninfected women; lower abdominal pain was present in 11 (18.3%) of HIV-infected and in 9 (15%) of HIV-uninfected women. This study showed that CTI is more prevalent among HIV-infected females as compared to HIV-uninfected females. As the use of real-time PCR is not feasible in most hospitals, efforts should be made to develop a simple, sensitive, and specific test to identify women with CTI for prevention of sequelae and HIV transmission.